(untitled) (Journal of EAHIL, 2018)
The number of systematic reviews and other types of reviews published worldwide to assist in clinical decision making is increasing rapidly. A large number of these studies point to the need for expert searching as an opportunity for librarians to develop a literature review search service as a key medical library service. The aims of the study are to analyse the review practices at the Institute of Oncology Ljubljana (systematic) and to identify the potential for establishing a comprehensive literature review support service. A quantitative analysis of the Institute’s 101 systematic reviews and 534 other review articles from 4 databases shows an increasing number of published articles from 2000 onwards. An analysis of 45 surveys identifies a high need for and expectation from librarians’ participation in the review process and in the research/clinical team.